Toxoplasma-proximal and distal control by GBPs in human macrophages. Issue 9 (21st December 2021) - Fisch, Daniel; Clough, Barbara; Khan, Rabia; Healy, Lyn; Frickel, Eva-Maria
ABSTRACT: Human guanylate binding proteins (GBPs) are key players of interferon–gamma (IFNγ)-induced cell intrinsic defense mechanisms targeting intracellular pathogens. In this study, we combine the well-established Toxoplasma gondii infection model with three in vitro macrophage culture systems to delineate the contribution of individual GBP family members to control this apicomplexan parasite. Use of high-throughput imaging assays and genome engineering allowed us to define a role for GBP1, 2 and 5 in parasite infection control. While GBP1 performs a pathogen-proximal, parasiticidal and growth-restricting function through accumulation at the parasitophorous vacuole of intracellular Toxoplasma, GBP2 and GBP5 perform a pathogen-distal, growth-restricting role. We further find that mutants of the GTPase or isoprenylation site of GBP1/2/5 affect their normal function in Toxoplasma control by leading to mis-localization of the proteins. Abstract : In human macrophages, guanylate binging protein 1, 2 and 5 (GBP1/2/5) control the growth of the parasite Toxoplasma gondii, with solely GBP1 targeting the parasite vacuole for elimination.